Amino-modified polystyrene nanoparticles affect signalling pathways of the sea urchin (Paracentrotus lividus) embryos. Issue 2 (7th February 2017) - Pinsino, Annalisa; Bergami, Elisa; Della Torre, Camilla; Vannuccini, Maria Luisa; Addis, Piero; Secci, Marco; Dawson, Kenneth A.; Matranga, Valeria; Corsi, Ilaria
Abstract: Polystyrene nanoparticles have been shown to pose serious risk to marine organisms including sea urchin embryos based on their surface properties and consequently behaviour in natural sea water. The aim of this study is to investigate the toxicity pathways of amino polystyrene nanoparticles (PS-NH2, 50 nm) in Paracentrotus lividus embryos in terms of development and signalling at both protein and gene levels. Two sub-lethal concentrations of 3 and 4 μg/mL of PS-NH2 were used to expose sea urchin embryos in natural sea water (PS-NH2 as aggregates of 143 ± 5 nm). At 24 and 48 h post-fertilisation (hpf) embryonic development was monitored and variations in the levels of key proteins involved in stress response and development (Hsp70, Hsp60, MnSOD, Phospho-p38 Mapk) as well as the modulation of target genes ( Pl-Hsp70, Pl-Hsp60, Pl-Cytochrome b, Pl-p38 Mapk, Pl-Caspase 8, Pl-Univin) were measured. At 48 hpf various striking teratogenic effects were observed such as the occurrence of cells/masses randomly distributed, severe skeletal defects and delayed development. At 24 hpf a significant up-regulation of Pl-Hsp70, Pl-p38 Mapk, Pl-Univin and Pl-Cas8 genes was found, while at 48 hpf only for Pl-Univin was observed. Protein profile showed different patterns as a significant increase of Hsp70 and Hsp60 only after 48 hpf compared to controls. Conversely, P-p38 Mapk protein significantly increased at 24 hpf and decreased at 48 hpf. Our findings highlight that PS-NH2 are able to disrupt sea urchin embryos development by modulating protein and gene profile providing new understandings into the signalling pathways involved.